Reinventing the antimicrobial pipeline in response to the global crisis of antimicrobial-resistant infections - Singer, A; Kirchhelle, C; Roberts, A (F1000Research, 2019)
The pipeline for new antibiotics is dry. Despite the creation of public/private initiatives like Combating Antibiotic Resistant Bacteria Biopharmaceutical Accelerator (Carb-X) and the Antimicrobial Resistance (AMR) Centre, the current focus on ‘push-pull’ incentives for the pharmaceutical industry still relies on economic return. We propose a joint, internationally-funded antimicrobial development institute that would fund permanent staff to take on roles previously assigned to pharmaceutical companies. This institute would receive ring-fenced, long-term, core funding from participating countries as well as charities, with the aim to focus on transforming the largely dormant antimicrobial pipeline. Resulting drugs would be sold globally and according to a principle of shared burdens. Our proposed model for antimicrobial development aims to maximise society’s investment, through open science, investment in people, and the sharing of intellectual property.